Study of the representative elementary volume of carbonate rocks and pore network simulation - Silva, Marianna Dantas da Silva (2019)
Carbonate reservoir characterization is an important challenge faced by the Brazilian O&G industry. In this context, the studies and simulation of three-dimensional digital rock models are being developed as a tool to aid in the petrophysical characterization of such rocks. This technology uses micro-computed tomography (micro-CT) images, which is a non-destructive method that allows the investigation of internal structure of rock at pore scale. The objective of this study is to use 3D digital rock models to understand the Representative Elementary Volume (REV) of heterogeneous carbonates, coquina and limestone rocks, simulate Pore Network Models (PNM) and from statistical analysis reproduce and simulate synthetic PNMs. Methodology that, may be used in further studies to upscale rocks’ pore space models. Additionally, the aim of this study is to develop 3D digital rock models that are correlate to different pore space characterization techniques such as micro-CT images and NMR T2 measurements. The rock samples were submitted to three laboratory measurements: routine core analysis, NMR T2 experiments, and micro-CT scans at different resolutions. The results of the 3D digital models include porosity and permeability estimations, simulation of PNMs, impact of image resolutions on models, analysis of pore size distributions, coordination number, REV study and the representative synthetic PNMs. Moreover, results for porosity and permeability obtained through simulations were compared to the laboratory measurements.